Perspectives on team communication challenges in caring for children with medical complexity - Sherri Adams; Madison Beatty; Clara Moore; Arti Desai; Leah Bartlett; Erin Culbert; Eyal Cohen; Jennifer Stinson; Julia Orkin (BMC, 2021)
Abstract Background Children with medical complexity (CMC) require the expertise of many care providers spanning different disciplines, institutions, and settings of care. This leads to duplicate health records, breakdowns in communication, and limited opportunities to provide comprehensive, collaborative care. The objectives of this study were to explore communication challenges and solutions/recommendations from multiple perspectives including (i) parents, (ii) HCPs - hospital and community providers, and (iii) teachers of CMC with a goal of informing patient care. Methods This qualitative study utilized an interpretive description methodology. In-depth semi-structured interviews were conducted with parents and care team members of CMC. The interview guides targeted questions surrounding communication, coordination, access to information and roles in the health system. Interviews were conducted until thematic saturation was reached. Interviews were audio-recorded, transcribed verbatim, and coded and analyzed using thematic analysis. Results Thirty-two individual interviews were conducted involving parents (n = 16) and care team members (n = 16). Interviews revealed 2 main themes and several associated subthemes (in parentheses): (1) Communication challenges in the care of CMC (organizational policy and technology systems barriers, inadequate access to health information, and lack of partnership in care) (2) Communication solutions (shared systems that can be accessed in real-time, universal access to health information, and partnered contribution to care). Conclusion Parents, HCPs, and teachers face multiple barriers to communication and information accessibility in their efforts to care for CMC. Parents and care providers in this study suggested potential strategies to improve communication including facilitating communication in real-time, universal access to health information and meaningful partnerships.